1994
DOI: 10.1001/archinte.1994.00420070055007
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mammographic Screening Relative to the Treatment of Women With Carcinoma of the Breast

Abstract: These results show that breast cancers detected in women who had undergone mammographic screening were more likely to be eligible for breast-conserving surgery and definitive breast irradiation compared with breast cancers detected in women who had not undergone mammographic screening. For women aged 50 years or more, there was a significant increase in the use of breast-conserving surgery and definitive breast irradiation for eligible breast cancers detected in women who had undergone mammographic screening c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This decrease may be attributable to any of several factors, such as the growing number of studies in which age has been shown to be an independent risk factor for local recurrence and the characterization of the BRCA1 and BRCA2 genes, which has made surgeons and patients, and especially younger patients, increasingly aware of familial breast carcinoma. Only a limited number of other studies have described the effects of breast carcinoma screening on breast‐conserving therapy, and those studies have reported conflicting results 30–32…”
Section: Discussionmentioning
confidence: 99%
“…This decrease may be attributable to any of several factors, such as the growing number of studies in which age has been shown to be an independent risk factor for local recurrence and the characterization of the BRCA1 and BRCA2 genes, which has made surgeons and patients, and especially younger patients, increasingly aware of familial breast carcinoma. Only a limited number of other studies have described the effects of breast carcinoma screening on breast‐conserving therapy, and those studies have reported conflicting results 30–32…”
Section: Discussionmentioning
confidence: 99%
“…26 This variability reflects several factors, including the years during which the study was conducted, the age of the study patients, the geographic location of the study, and the socioeconomic status of the patients. [27][28][29] In contrast, eligibility for BCT approaches 90% in women who have mammographically detected breast cancer. 29 The rate of positive margins following the initial surgical procedure was estimated at 10%, reflecting our institutional experience.…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29] In contrast, eligibility for BCT approaches 90% in women who have mammographically detected breast cancer. 29 The rate of positive margins following the initial surgical procedure was estimated at 10%, reflecting our institutional experience. The frequency of margin positivity following NLB varies in the literature from 5% to 90%.…”
Section: Methodsmentioning
confidence: 99%
“…11 Numerous uncontrolled trials and retrospective studies have documented the importance of mammographic screening in diagnosing small, early-stage breast cancers. [12][13][14][15][16] Early diagnosis leads to identification of breast cancer at an earlier stage and grade and therefore allows more women to be eligible for breast-conserving treatment (BCT), the standard of care for women with early-stage breast cancer. 12 Therefore, in the interest of examining BCT eligibility, this study will also look at the staging of breast tumors.…”
mentioning
confidence: 99%